2003
DOI: 10.1002/ijc.10968
|View full text |Cite
|
Sign up to set email alerts
|

Decreased DNA repair gene expression among individuals exposed to arsenic in United States drinking water

Abstract: Arsenic is well established as a human carcinogen, but its precise mechanism of action remains unknown. Arsenic does not directly damage DNA, but may act as a carcinogen through inhibition of DNA repair mechanisms, leading indirectly to increased mutations from other DNA damaging agents. The molecular mechanism underlying arsenic inhibition of nucleotide excision repair after UV irradiation (Hartwig et al., Carcinogenesis 1997;18:399 -405) is unknown, but could be due to decreased expression of critical genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 41 publications
7
86
0
Order By: Relevance
“…Similar findings were reported by Cheng et al (59) and Wei et al (60) they found that low mRNA levels of DNA-repair genes (including ERCCC1 and ERCC2) in lymphocytes were associated with high relative risk for head and neck cancer and lung cancer. The decreased expression of ERCC1 by AA treatment is also in accordance to the study in which arsenic can diminish the expression of the nucleotide excision repair genes ERCC1, XPF (ERCC4), and XPB (ERCC3) (61). Another DNA repair gene, MGMT (O-6-methylguanine-DNA methyltransferase), was downregulated in 30 μM AA treatment but this result is opposite to that in AA-treated rats (44).…”
Section: ------------------------------------------------------------supporting
confidence: 86%
“…Similar findings were reported by Cheng et al (59) and Wei et al (60) they found that low mRNA levels of DNA-repair genes (including ERCCC1 and ERCC2) in lymphocytes were associated with high relative risk for head and neck cancer and lung cancer. The decreased expression of ERCC1 by AA treatment is also in accordance to the study in which arsenic can diminish the expression of the nucleotide excision repair genes ERCC1, XPF (ERCC4), and XPB (ERCC3) (61). Another DNA repair gene, MGMT (O-6-methylguanine-DNA methyltransferase), was downregulated in 30 μM AA treatment but this result is opposite to that in AA-treated rats (44).…”
Section: ------------------------------------------------------------supporting
confidence: 86%
“…For example, the following DNA repair genes were altered after arsenic treatment: Xeroderma pigmentosum group D-complementing protein (XPD, DNA excision repair protein ERCC2), Xeroderma pigmentosum group C-complementing protein (XPC), AP endonuclease 1 (APE1), DNA ligase-1 (DNL1), DNA polymerase delta catalytic subunit (DPD), DNA topoisomerase II alpha (TOP2A), DNA damage-inducible protein GADD45 (Chen et al 2000;Liu et al 2001 replication licensing factors 2 and 7 (MCM2, MCM7), proliferating cyclic nuclear antigen (PCNA), O 6 -methylguanine-DNA methyltransferase (MGMT), replication factor C large and 40-kDa subunits (RFC, RFC40), and uracil-DNA glycosylase precursor (UNG1). Other studies in our laboratory using human lymphocytes from an epidemiologic study have demonstrated a dose-dependent correlation between decreased expression of nucleotide excision repair genes and chronic exposure to arsenic in the drinking water (Andrew et al 2003). Surprisingly, increasing the dose of arsenic to 50 µM did not simply increase the magnitude of the change in the same set of genes or add additional genes.…”
Section: Mip2-αmentioning
confidence: 69%
“…For example, inorganic arsenic alone has been consistently negative for carcinogenesis in animal bioassays, but arsenic in drinking water greatly enhances the tumorigenicity of ultraviolet radiation in a mouse model (33). Similar synergistic or potentiating effects of arsenic have been seen for endocrine disruption (6,16), angiogenesis (17,38), and DNA damage and repair (3,13). Human epidemiology studies also have shown that arsenic is strongly synergistic with cigarette smoking for risk of lung cancer (10,37).…”
Section: Discussionmentioning
confidence: 94%